2024
DOI: 10.3390/jrfm17020077
|View full text |Cite
|
Sign up to set email alerts
|

Volatility and Herding Bias on ESG Leaders’ Portfolios Performance

Nektarios Gavrilakis,
Christos Floros

Abstract: We here analyze the factor loadings given by the CAPM, the Fama–French three (FF3), and the five-factor model (FF5), and test the performance and the validity of adding two more factors (volatility and dispersion of returns) to the FF5 factor model of European index-based ESG leaders’ portfolios. Our ESG leaders’ portfolios generated significant negative alphas during 2012–2022, corroborating the literature’s negative argument. The negative abnormal returns of ESG leaders’ portfolios are homogeneous across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
1
0
0
Order By: Relevance
“…Chen and Gao (2020) employed a Fama and French three-factor model to examine how three defined volatility risk factors derived from VIX may affect the pricing of assets. In a recent paperGavrilakis and Floros (2024) by implying the CAPM, FF3, FF5 methodologies reported that European and Global indexes based ESG leaders' portfolios produce negative abnormal returns during 2012-2022, verifying the reports of previous studies and deduced that European ESG portfolios are tilt towards large cap, robust operating profitability and against aggressive investment.…”
supporting
confidence: 66%
“…Chen and Gao (2020) employed a Fama and French three-factor model to examine how three defined volatility risk factors derived from VIX may affect the pricing of assets. In a recent paperGavrilakis and Floros (2024) by implying the CAPM, FF3, FF5 methodologies reported that European and Global indexes based ESG leaders' portfolios produce negative abnormal returns during 2012-2022, verifying the reports of previous studies and deduced that European ESG portfolios are tilt towards large cap, robust operating profitability and against aggressive investment.…”
supporting
confidence: 66%